2013
DOI: 10.1371/journal.pone.0074984
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Timing during Ontogeny Matter: Effects of a Temporary High Temperature on Survival, Body Size and Colouration in Harmonia axyridis

Abstract: The ambient temperature experienced during development is a crucial factor affecting survival and adult phenotype in ectotherms. Moreover, the exact response of individuals to different temperature regimes is frequently sex-specific. This sex-specific response can result in varying levels of sexual dimorphism according to the experienced conditions. The majority of studies have investigated the effects of temperature on individuals reared under a constant temperature regime throughout their whole preimaginal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 73 publications
2
57
0
1
Order By: Relevance
“…In addition to reproduction, morphological traits were impacted more by heat stress closer to adult stage than at earlier stages. In the Coleoptera species, Harmonia axyridis, adult body size and coloration were affected by heat stress at the 4 th -instar larval or pupal stages but not at early development stages42. Moreover, in the butterfly, Bicyclus anynana , wing pattern was sensitive only to late larval stage temperatures43.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reproduction, morphological traits were impacted more by heat stress closer to adult stage than at earlier stages. In the Coleoptera species, Harmonia axyridis, adult body size and coloration were affected by heat stress at the 4 th -instar larval or pupal stages but not at early development stages42. Moreover, in the butterfly, Bicyclus anynana , wing pattern was sensitive only to late larval stage temperatures43.…”
Section: Discussionmentioning
confidence: 99%
“…Our data clearly indicate that eggs and hatchlings are very sensitive to heat while others such as pupae are less susceptible. Some other studies also showed variation in heat resistance throughout ontogeny, indicating large differences with respect to the most heat‐tolerant developmental stage ranging from early via intermediate up to late ones (Krebs & Loeschcke, ; Abdelghany et al ., ; Amarasekare & Sifuentes, ; Knapp & Nedvěd, ).…”
Section: Discussionmentioning
confidence: 99%
“…These hypotheses have been supported in laboratory experiments. For example, exposing early life-stages of P. xylostella (Xing et al 2014;Zhang et al 2015), eggs of Manduca sexta and Wyeomyia smithii (Zani et al 2005) and early instar nymphs/larvae of Metopolophium dirhodum (Ma et al 2004b) and Harmonia axyridis (Knapp and Nedvěd 2013) to acute [i.e. high amplitude but short duration (few hours)] heat stress did not affect female fecundity or adult phenotype.…”
Section: Carry-over Effects Of High Temperatures In Organisms With Comentioning
confidence: 99%